Electrical Generation and Deletion of Magnetic Skyrmion‐Bubbles via Vertical Current Injection (Adv. Mater. 45/2021). Issue 45 (9th November 2021) - Yang, Seungmo; Moon, Kyoung‐Woong; Ju, Tae‐Seong; Kim, Changsoo; Kim, Hyun‐Joong; Kim, Juran; Tran, Bao Xuan; Hong, Jung‐Il; Hwang, Chanyong
Abstract : Skyrmion Generation/Deletion The generation/deletion of magnetic skyrmions at a specific area on a device is the most demanding issue in skyrmionics. In article number 2104406, Chanyong Hwang and co‐workers introduce a recipe for magnetic skyrmion generation/deletion. A vertically injected current pulse induces skyrmion generation/deletion one by one depending on the polarity. Using this vertical‐current concept with a spin–orbit‐torque‐driven skyrmion shifting, a proof‐of‐concept demonstration of skyrmion racetrack memory is presented.